COMPARATIVE ANALYSIS OF BONE HEALING UNDER PHYSIOLOGICAL AND TRACE ELEMENT OVERLOAD CONDITIONS IN SENILE RATS - Lohvyniuk, Hanna; Husak, Yevheniia; Vynnychenko, Ihor; Solodovnyk, Oleksandr (Eastern Ukrainian Medical Journal, 2025)
Introduction. Age-related impairment of bone healing is a growing clinical concern. While the role of trace elements in bone metabolism is well recognized, their effect on cancellous bone regeneration in elderly organisms remains poorly understood. Our study contributes a valuable foundation for understanding how excess exposure to specific trace elements – namely zinc (Zn), manganese (Mn), copper (Cu), lead (Pb), and chromium (Cr) – affects bone regeneration. Through a comparative histological and ultrastructural analysis of fracture healing in control and microelement-overload groups, we aim to elucidate the mechanisms by which trace elements modulate bone repair, angiogenesis, and osteogenesis in aged organisms. Methods. Our study was focused on comparing the course of cancellous bone healing under physiological conditions and trace element overconsumption in senile rats using histological and scanning electron microscopy analysis.Results. The results showed cancellous bone healing of control group followed a time-dependent sequence of inflammation, granulation tissue formation, fibroreticular remodeling, and coarse woven bone deposition. In contrast, the trace element overconsuption group exhibited delayed and disorganized reparative osteogenesis, marked by delay tissue formation, prolonged inflammatory features, and substantial cartilaginous tissue formation by day 21. Reduced vascular density in MeG animals suggested impaired angiogenesis, further contributing to compromised regeneration.Conclusions. Trace element overconsumption alters the normal trajectory of cancellous bone healing in senile rats, inducing a shift toward endochondral ossification and impairing vascularization. These findings underscore the critical influence of microelement balance on skeletal repair in aging organisms.